Pelatihan Pemanfaatan Bunga Telang menjadi Minuman Herbal bersama PKK Desa Sungai Buaya - Furqon, Imam; Afifah, Afifah; Oktavianti, Alina; Azizah, Annida Nurul; Harlinda, Ayu; Martha Fadila, Bella; Wulandari, Cessi; Sanzela, Dea Fitsia; Efryanty, Efryanty; Ervina, Ervina; Parita, Faza Hasya; Wiyono, Ketang (Penerbit Goodwood, 2025)
Purpose: This service aimed to empower PKK members in Sungai Buaya Village by providing practical knowledge and skills to process butterfly pea flowers (Clitoria ternatea) into healthy herbal drinks. The goal was to promote a healthy lifestyle and create opportunities for home-based businesses using local resources. Methodology/approach: The method used was a participatory and educational workshop. Data were collected through observation, pre-surveys, structured questionnaires, and open interviews to evaluate the effectiveness of the training. Results/findings: The training successfully increased participants’ understanding of the health benefits of butterfly pea flowers and their ability to process them into herbal drinks. All 20 participants stated that they were able to make and package the product independently after the session. The evaluation showed a 100% positive response in knowledge, skills, and satisfaction levels, indicating strong community enthusiasm and potential for entrepreneurial development. Conclusion: The service effectively enhanced the participants' knowledge, skills, and motivation to utilize butterfly pea flowers for health and economic purposes. The success of the training suggests that similar community-based programs should be expanded and sustained, especially with additional sessions on ready-to-drink product development and small-scale marketing strategies. Limitations: Kendala utama meliputi durasi pelatihan yang singkat serta keterbatasan fasilitas yang menghambat penerapan mandiri hasil pelatihan. Contributions: This program contributes to empowering women through local resource utilization and provides a practical model for participatory training to develop community-based herbal products.